Factors Affecting the Public Judgement of Consumer Protection Authorities - Csiszár, Csilla Margit (Theory, Methodology, Practice – Review of Business and Management, 2012)
The article first introduces the state-provided institutions for consumer protection in Hungary, then examines and systematises those factors having a significant impact on the public judgement of the work of consumer protection authorities. The study is based on the presumption that the public judgement of the work of consumer protection institutions is affected by many factors, and that these factors can be grouped and counted. After examining the main fields of activities of consumer protection institutions and the main factors and aspects affecting the judgement of the public, a model for the measurement of satisfaction is proposed.